Universal Sewing Machine Vibration Protection Methods - Kurbanova Iroda Ixtiyorovna (Zien Journals, 2021)
This article describes the methods and tools for reducing and protecting vibration encountered in the universial sewing machine.Vibration protection is understood to be carried out by reducing the level of vibration in the object being protected, the vibration emanating from the source.
Keywords: Sewing machine; vibration; strut; needle; needle mechanism; thread; deformation; amplitude